A Review on Acrylate-Terminated Urethane Oligomers and Polymers: Synthesis and Applications. Issue 7 (3rd May 2018) - Maurya, Shyam Dev; Kurmvanshi, S. K.; Mohanty, S.; Nayak, Sanjay K.
ABSTRACT: Polyurethane-acrylate oligomers are a new class of polyurethane which are produced by the reaction of polyols with diisocyanate and capped by acrylate. There is a growing demand for modification with improved properties of the polyurethane-acrylate. This review covers the following topic: structure, modification of polyurethane-acrylate backbone, reactive diluents, curing, mechanical, optical, thermal behavior, and applications presented herein. The basic understanding of the chemistry and mechanistic aspects of these oligomers has reached a level was tailor-made formulations suitable for a particular application may be selected. GRAPHICAL ABSTRACT: